LEK BEHAVIOR of THE PLOVERCREST (STEPHANOXIS LALANDI, TROCHILIDAE) - Pizo, Marco Aurelio [UNESP] (Wilson Ornithological Soc, 2012)
I examined the lek structure and behavior of male Plovercrests (Stephanoxis lalandi) at a lek in southern Brazil. The lek included seven territorial males; the distance between neighboring lek territories was 14.8 +/- 6.3 m. Territory size was 11.4 +/- 4.4 m(2). Territory size and distance between territories were among the lowest reported for Trochilinae hummingbirds. Lek attendance by territory owners fluctuated throughout the day. Activity slowly diminished after an initial period of activity after arrival at sunrise, but increased again between 0900 and 1500 hrs. All males left their territories by 1830 hrs. Males sang at a similar rate (74.8 +/- 14.5 songs/min) throughout the lekking season, but not throughout the day. There was no relationship between lek attendance and singing rate, two parameters that potentially affect mating success in lekking birds. Considerable interspecific variation occurs among lekking trochilines, indicating that much remains to be investigated about lek behavior and structure in hummingbirds. Received 11 March 2011. Accepted 30 August 2011.